2014
DOI: 10.1098/rsif.2014.0902
|View full text |Cite
|
Sign up to set email alerts
|

Design of a biochemical circuit motif for learning linear functions

Abstract: Learning and adaptive behaviour are fundamental biological processes. A key goal in the field of bioengineering is to develop biochemical circuit architectures with the ability to adapt to dynamic chemical environments. Here, we present a novel design for a biomolecular circuit capable of supervised learning of linear functions, using a model based on chemical reactions catalysed by DNAzymes. To achieve this, we propose a novel mechanism of maintaining and modifying internal state in biochemical systems, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…McGregor et al [42] demonstrated how in silico evolution can be used used to develop artificial chemistries capable of learning some particular fixed function. Lakin et alʼs scheme for rudimentary learning in an enzymatic chemistry [34] is equivalent to non-negative least-squares regression and achieves learning within a chemical system (and similarly for our more recent learning scheme based on buffered DNA strand displacement chemistry [35,36]). Our FCNN differs from these architectures in two important ways.…”
Section: Related Workmentioning
confidence: 79%
See 1 more Smart Citation
“…McGregor et al [42] demonstrated how in silico evolution can be used used to develop artificial chemistries capable of learning some particular fixed function. Lakin et alʼs scheme for rudimentary learning in an enzymatic chemistry [34] is equivalent to non-negative least-squares regression and achieves learning within a chemical system (and similarly for our more recent learning scheme based on buffered DNA strand displacement chemistry [35,36]). Our FCNN differs from these architectures in two important ways.…”
Section: Related Workmentioning
confidence: 79%
“…Several groups have designed chemical systems based on learning models other than neural networks, such as decision trees [48] and least-squares regression (LSR) [34]. McGregor et al [42] demonstrated how in silico evolution can be used used to develop artificial chemistries capable of learning some particular fixed function.…”
Section: Related Workmentioning
confidence: 99%
“…We have produced circuits that decode broadly relevant but predetermined temporal features. Going forward, it would be interesting to develop molecular circuits that can learn relevant temporal features dynamically as in machine learning approaches. In the learning paradigm, for example, a molecular circuit could be exposed to two classes of time-varying patterns during a “training phase” (the temporal equivalent of cat and dog images in static pattern recognition).…”
Section: Discussionmentioning
confidence: 99%
“…With one additional circuit component that actives weight molecules during a supervised training process, the DNA circuits would be capable of activating a specific set of wires in the weight-multiplication layer when exposed to a specific set of patterns. As widely discussed in experimental 27 and theoretical [28][29][30] studies, learning-the most desirable property Fig. 4 | A winner-take-all DNA neural network that recognizes 100-bit patterns as one of nine handwritten digits.…”
Section: Letter Researchmentioning
confidence: 99%